Modeling and measuring dielectric constants for very thin materials using a coaxial probe - You, Kok Yeow; Abbas, Zulkifly; Lee, Chia Yew; Abd Malek, Mohd Fareq; Lee, Kim Yee; Cheng, Ee Meng (Radioengineering Society, 2014)
This paper is focused on the non-destructive measurement of the dielectric constants (relative permittivities) of thin dielectric material (0.1-0.5 mm) using an open-ended coaxial probe with an outer diameter of 4.1 mm. Normalized de-embedding and network error calibration procedures were applied to the coaxial probe. The measured reflection coefficients for the thin samples were taken with a vector network analyzer up to 7 GHz, and the calibrated reflection coefficients were converted to relative dielectric constants using an empirical reflection coefficient model. The empirical model was created using the regression method and expressed as a polynomial model, and the coefficients of the model were obtained by fitting the data using the Finite Element Method (FEM).